Nutritional Behaviour is a Social Problem in the Modern Lifestyle - Laura, Bissenbayeva; Diana, Kalieva; Lyazzat, Abdulina; Zhanat, Bissenbayeva (Journal of Nutritional Therapeutics, 2019)
The purpose of this study is to observe, analyze, compare and educate young people's dietary behaviour. It was noticed that the consumption of fruits and vegetables is low, restricted in many cases to one or two servings per day. This result led to the conclusion that healthy food does not play an important role in young people's eating habits. Given this situation, in a few years, childhood obesity rates could rise alarmingly. The nutrition factors contemplated were: the motivation of young people for a healthy diet; the information they possess about correct nutrition habits and their attitudes for a healthy lifestyle.